GP reimbursement and visiting behaviour in Ireland - David Madden; Anne Nolan; Brian Nolan (University College Dublin, Department of Economics, 2004)
In Ireland, approximately 30 per cent of the population (“medical cardholders”) receive free GP services while the remainder (“non-medical cardholders”) must pay for each visit. In 1989, the manner in which GPs were reimbursed by the State for their medical cardholder patients was changed from fee-for-service to capitation while other patients continued to pay on a fee-for-service basis. Concerns about supplier-induced demand were in part responsible for this policy change. The purpose of this paper is to examine the extent to which the utilisation of GP services is influenced by the reimbursement system facing GPs, by comparing visiting rates for the two groups before and after this change. Using a difference-in-differences approach on pooled micro-data from 1987, 1995 and 2000, we find that medical card eligibility exerts a consistently positive and significant effect on the utilisation of GP services. However, the differential in visiting rates between medical cardholders and others did not narrow between 1987 and 1995 or 2000, as might have been anticipated if supplier-induced demand played a major role prior to the change in reimbursement system.
hdl:10197/795
Keywords: 330; GP Utilisation; Reimbursement; Supplier-Induced Demand; Difference-in-Differences